The Relationship Between Maternal Knowledge and Attitudes and The Incidence of Diarrhea - Marbun, Ria Angelina; Juliyanti, Juliyanti; Marintan, Heny (Jurnal Keperawatan Priority, 2024)
Diarrhea is a disease that we often encounter in society and in developing countries and is a cause of death in children under five which is usually caused by contaminated food and drink. for drinking habits. poor clean living. The aim of this study was to determine the relationship between maternal knowledge and attitudes and the incidence of diarrhea in toddlers in the pediatric inpatient ward at Immanuel Hospital, Bandung. This research is a quantitative research with a cross sectional approach. The sampling technique for this research was accidental sampling with a total sample of 64 mother respondents. The research instrument used a questionnaire. The results of univariate analysis show that almost all respondents (71.9%) have good knowledge and almost all respondents (69.7%) have a supportive attitude (Favorable). The results of the bivariate analysis obtained a p-value of 0.03, which is smaller than 0.05, so it can be concluded that there is a significant relationship between mother's knowledge and attitudes and the incidence of diarrhea in toddlers in children's inpatient rooms. It is recommended that hospitals can further improve the promotion of disease prevention health services. diarrhea in mothers of toddlers, to increase understanding about diarrheal disease so that recurrent diarrhea does not occur in toddlers which can lead to death.